2021
DOI: 10.14740/jcgo752
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Effects of the Coronavirus Disease 2019 Pandemic on Pregnant and Postpartum Women

Abstract: Background: There is little research available regarding the psychological effect of the coronavirus disease 2019 (COVID-19) pandemic on antenatal and postnatal women in the Middle East. This study aimed to evaluate the burden of the pandemic on the mental health of pregnant and postpartum women in Oman. Methods:A cross-sectional study was carried out from July to December 2020 at the Sultan Qaboos University Hospital in Muscat, Oman. A previously validated Arabic version of the Depression, Anxiety, and Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…A contradicting study conducted by Effati-Daryani [17] revealed that age more than 35 years was linked to increased stress levels. On the other hand, a study conducted by AL Sumri [18] to assess the impact of the pandemic on pregnant and postpartum women in Oman reported that no significant associations were found between age and stress symptoms during the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…A contradicting study conducted by Effati-Daryani [17] revealed that age more than 35 years was linked to increased stress levels. On the other hand, a study conducted by AL Sumri [18] to assess the impact of the pandemic on pregnant and postpartum women in Oman reported that no significant associations were found between age and stress symptoms during the pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…10 Different studies conducted in various parts of the world have reported a wide variety of prevalence of anxiety among pregnant women. Some of the reported prevalence of anxiety are as follows: 39.1% in Nepal, 11 11.1% in India, 12 36.77% in China, 13 37.5% in Nigeria, 14 29.7% in Oman, 15 29.2% in Turkey, 16 and 52% in Netherlands. 17 The prevalence of anxiety reported in this study is lower than most of the other studies conducted in Nepal and other parts of the world.…”
Section: Discussionmentioning
confidence: 99%